Reinstating Elective Surgeries in MedStar Health: A Roadmap for Healthcare Organizations. Issue 1 (11th September 2020) - Stein, David E.; Chia, Stanley H.; Breakey, Thomas H.; Song, David H.; Woo, Edward Y.; Fairbanks, Rollin J.; Jordan, David; Curl, Leigh Ann; Boucher, Henry R.; Boyle, Lisa; Edwards, Karol; Friedrich, Hanna; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Coronavirus disease 2019 (COVID-19) infections have strained hospital resources worldwide. As a result, many facilities have suspended elective operations and ambulatory procedures. As the incidence of new cases of COVID-19 decreases, hospitals will need policies and algorithms to facilitate safe and orderly return of normal activities. We describe the recommendations of a task force established in a multi-institutional healthcare system for resumption of elective operative and ambulatory procedures applicable to all hospitals and service lines. Methods: MedStar Health created a multidisciplinary task force to develop guidelines for resumption of elective surgeries/procedures. The primary focus areas included the establishment of a governance structure at each healthcare facility, prioritization of elective cases, preoperative severe acute respiratory syndrome coronavirus 2 testing, and an assessment of the needs and availability of staff, personal protective equipment, and other essential resources. Results: Each hospital president was tasked with establishing a local perioperative leadership team answering directly to them and granted the authority to prioritize elective surgery and ambulatory procedures. An elective surgery algorithm was established using a simplified Medically Necessary Time Sensitive score, with multiple steps requiring a "go/no-go" assessment based on local resources. In addition, mandatory preoperative COVID testing policies were developed and operationalized. Conclusions: Even when the COVID pandemic has passed, hospitals and surgical centers will require COVID screening and testing, case prioritization, and supply chain management to provide care essential to the surgical patient while protecting their safety and that of staff. Our guidelines consider these factors and are applicable to both tertiary academic medical centers and smaller community facilities.